Ossifying fibroma as a cause of blindness in a 5‐year‐old Quarter Horse gelding. (28th May 2018) - Madrigal, R. G.; Friedemann, M. C.; Vallone, J. M.; Ruoff, C. M.; Vallone, L. V.; Laughrey, T.; Rech, R. R.; Coleman, M. C.
Summary: A 5‐year‐old Quarter Horse gelding presented to Texas A&M University Veterinary Medical Teaching Hospital with a several week history of bilateral blindness. Neurological deficits included an absent menace response and severe atrophy of the optic nerve head in the left eye (OS) as well as decreased vision in the right eye (OD). Advanced imaging consisting of computed tomography (CT) and magnetic resonance imaging (MRI) confirmed a large mass in the base of the skull invading the sinuses and asymmetrically compressing the optic nerves rostral to the optic chiasm. Due to the size and location of the mass as well as severity of associated neurological signs, humane euthanasia was elected. Necropsy examination identified a large mass effacing the sphenopalatine sinuses and compressing the optic nerves. Histologically, the mass was identified as an ossifying fibroma (OF) and degeneration of the optic nerves was confirmed. As an OF in this location has never been described in a horse, this case demonstrates a new differential for blindness in horses.